Corporate memory: A memory compaction mechanism towards Malaysia's leading companies' transparent governance/ Aiman Putra Amran... [et al.] - Amran, Aiman Putra; Madzli, Muhammad Suffian; Airulanuar, Muhammad Akif; Muhidin, Muhammad Hazim (2015)
The purpose of conducted this research is to know that on how corporate memory affect towards to the organization. We have chosen four organizations that suitable for completing our research which is MMIJ, MSC, MATRADE and PETRONAS which applying ICT in their organization. This research is about on how corporate memory plays their role towards to the organization that has been mentioned above. This wants to ensure that is corporate memory need to be preserved for the future usage. By preserving corporate memory organization can achieve their goals and standard. Other than that, quality performance of work such as ICT facilities, knowledge sharing and ICT impact can be improvise by having corporate memory in the organization. Therefore, corporate memory is very important to be preserve and maintain for long term performance of works and quality. Hence, the organization can reach their goals and standards.